Debt Maturity and Commitment to Firm Policies - Gamba, Andrea; Saretto, Alessio (The Review of Corporate Finance Studies, 2026)
Abstract When firms can issue debt at discrete dates only, debt maturity becomes an effective tool to constrain investment and debt policies. In the absence of other frictions, single-period debt restores first-best investment. With market freezes, long-maturity debt amplifies underinvestment and the leverage ratchet effect, while short maturity mitigates these distortions. Calibrating the model to U.S. nonfinancial firms shows that choosing the optimal debt maturity can reduce the cost of commitment problems and market frictions by up to 4% of firm value. A decomposition of the equilibrium credit spread reveals that the component associated with time-inconsistent debt and investment policies is largest when leverage and default risk are low, and is substantially reduced by shorter debt maturities. (JEL G12, G31, G32, E22)